Study Literature Review of Financial Analysis on PT Bluebird In Medan City - Sri Siregar; Tanti Sembiring; Tia Sucipto (Jurnal Ekonomi, Manajemen, Akuntansi dan Keuangan, 2025)
This study aims to analyse the financial performance of PT Blue Bird in Medan City within [time span]. The analysis was conducted using financial ratios, such as liquidity, solvency, profitability, and activity. The results showed that PT Blue Bird has good financial performance indicated by high profitability ratios]. Factors affecting the financial performance of PT Blue Bird were also identified, such as business competition, government regulations, and technological developments. This research is expected to contribute to a better understanding of the financial performance of transport companies in Indonesia, especially PT Blue Bird.